2016
DOI: 10.1155/2016/6432492
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Synthesis Catalyst and Complex Metal Ion: Multicomponent Synthesis of 1,3-Bis(4-phenyl-[1,2,3]triazol-1-yl)-propan-2-ol Copper(I) Complex and Application in Copper-Catalyzed Alkyne-Azide Cycloaddition

Abstract: A new bistriazole copper complex was synthesized by direct treatment of an alkyne, an azide, and CuI as copper salt throughin situligand formation under a multicomponent reaction process. This complex was analyzed by XPS, TGA, DSC, and SEM techniques and revealed a triangular-shaped morphology, high thermal stability, and catalytic power in CuAAC reactions, requiring only 2.5% mol catalyst to afford 1,2,3-triazoles in good yields which can be reused at least for 4 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Thus, the successively addition of Fehling A and B solutions to a mixture glucose-phenylacetylene produced a characteristic yellow precipitate which was identified as phenylethynylcopper (I) 1 presenting the same physical data described in literature (Scheme 1) [12,13]. In addition, XPS analysis of compound 1 displays a signal 2p 3/2 at 935 eV corresponding to a copper species with oxidation number (I) in agreement to previous reports (Figure 1) [10,14], whereas a signal at 533.8 eV (spectrum b, Figure 1) suggests a Cu-C interaction [15,16]; moreover, C 1s bond energy at 285.8 eV assigned to aromatic carbons confirmed the formation of copper (I) phenylacetylide 1 which was used in following steps. The reaction between 1-ethynylcyclohexanol 2 and benzylazide 3 was used as model to evaluate the catalytic activity of phenylacetylide 1 (Scheme 2).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the successively addition of Fehling A and B solutions to a mixture glucose-phenylacetylene produced a characteristic yellow precipitate which was identified as phenylethynylcopper (I) 1 presenting the same physical data described in literature (Scheme 1) [12,13]. In addition, XPS analysis of compound 1 displays a signal 2p 3/2 at 935 eV corresponding to a copper species with oxidation number (I) in agreement to previous reports (Figure 1) [10,14], whereas a signal at 533.8 eV (spectrum b, Figure 1) suggests a Cu-C interaction [15,16]; moreover, C 1s bond energy at 285.8 eV assigned to aromatic carbons confirmed the formation of copper (I) phenylacetylide 1 which was used in following steps. The reaction between 1-ethynylcyclohexanol 2 and benzylazide 3 was used as model to evaluate the catalytic activity of phenylacetylide 1 (Scheme 2).…”
Section: Resultssupporting
confidence: 89%
“…In conjunction with other research, we observed in situ formation of 1,2,3-triazole copper complexes by a straightforward mixing of alkyne, azide and a copper (I) salt [10]. From these studies, we detected the formation of a copper acetylide and we decided to investigate in detail this process aimed to prepare efficient catalysts for the synthesis of 1,2,3-triazoles through CuAAC reactions.…”
Section: Introductionmentioning
confidence: 69%
“…The use of copper complexes in various chemical reactions, such as alkyne–azide cycloaddition, 33 hydroboration reactions, 34 allylic alkylation reactions, 35 direct addition of terminal alkynes to imines, 36 and β-boration of α,β-unsaturated esters, 37 has led us to the use of these compositions as a catalyst in this reaction.…”
Section: Introductionmentioning
confidence: 99%